Physiological Differences in Bleaching Response of the Coral Porites astreoides Along the Florida Keys Reef Tract During High-Temperature Stress - Lenz, Elizabeth Ann; Bartlett, Lucy A.; Stathakopoulos, Anastasios; Kuffner, Ilsa B. (Frontiers in Marine Science, 2021)
The Florida Keys reef tract (FKRT) has a unique geological history wherein Holocene sea-level rise and bathymetry interacted, resulting in a reef-building system with notable spatial differences in reef development. Overprinted on this geologic history, recent global and local stressors have led to degraded reefs dominated by fleshy algae, soft corals, and sponges. Here, we assessed how coral physiology (calcification rate, tissue thickness, reproduction, symbiosis, and bleaching) varies seasonally (winter vs. summer) and geographically using 40 colonies of the mustard hill coral Porites astreoides from four sites across 350 km along the FKRT from 2015 to 2017. The study coincided with a high-temperature event in late summer 2015 that caused heterogeneous levels of coral bleaching across sites. Bleaching severity differed by site, with bleaching response more aligned with heat stress retroactively calculated from local degree heating weeks than those predicted by satellites. Despite differences in temperature profiles and bleaching severity, all colonies hosted Symbiodiniaceae of the same genus (formerly Clade A and subtypes). Overall, P. astreoides at Dry Tortugas National Park, the consistently coolest site, had the highest calcification rates, symbiont cell densities, and reproductive potential (all colonies were reproductive, with most planula larvae per polyp). Corals at Dry Tortugas and Fowey Rocks Light demonstrated strong seasonality in net calcification (higher in summer) and did not express visual or partial-mortality responses from the bleaching event; in contrast, colonies in the middle and southern part of the upper keys, Sombrero Key and Crocker Reef, demonstrated similar reduced fitness from bleaching, but differential recovery trajectories following the heat stress. Identifying reefs, such as Dry Tortugas and possibly Fowey Rocks Light that may serve as heat-stress refugia, is important in selecting candidate sites for adaptive reef-management strategies, such as selective propagation and assisted gene flow, to increase coral-species adaptation to ocean warming.